Because of the rabbit - Lord, Cynthia (Scholastic Press, 2019)
On the last night of summer, Emma and her Maine game warden father rescue a small domestic rabbit stuck in a fence; the very next day Emma starts fifth grade after years of being home schooled, excited and apprehensive about making new friends, but she is paired with Jack, a hyperactive boy, who does not seem to fit in with anyone--except that they share a love of animals, which draws them together, because of the rabbit.